Physicochemical Characteristics of Butterfly Pea Flower Petals Steep Obtained at Different Steeping Temperature and Time - Lucia Soedirga; Intan C Matita; Jessica Sidharta (Reaktor, 2023)
Flower is an important part of the plant containing phytochemical compounds, especially the phenolic acids, flavonoids, and anthocyanin that can be used as natural antioxidants. Phytochemical compounds are usually drawn by steeping the flower petals in hot water. Indeed, different temperatures and steeping times would affect the yield of phytochemicals obtained. The butterfly pea flower is one of edible flowers that brings antioxidant activity due to the presence of phytochemical compounds, namely flavonoids and phenolic acids. Nevertheless, there have been limited studies dedicated to the search of steeping condition of butterfly pea flower petals in water. Thus, this study aimed to determine the time and temperature of steeping to produce the butterfly pea step with preferred physicochemical characteristics. The result indicates that butterfly pea flower petals which undergo steeping at 60°C for 45 minutes produce antioxidant activity with an IC50 value of 251.89 ± 32.02 ppm. Furthermore, the butterfly pea flower steep produced had blue to purple color with °Hue of 277.06 ±2.55, 1.23 ± 0.07 mg/L of total monomeric anthocyanin content, 6.83 ± 0.02 of pH and 138.42 ± 15.88 mg GAE / g sample of total phenolic content. Keywords: antioxidant; butterfly pea flower; steep; temperature; time